Loss assessment of group residential buildings and information management system for wind catastrophe. Issue 180 (September 2018) - Wang, Guoxin; Li, Mingxin
Abstract : Available online 21-Feb-2018. This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of < We were notified via Springer of a complaint that papers published in Natural Hazards and INDAER had significant overlap. As the Elsevier publication was the second publication we took the investigation on to see if the second publication was justified. The EiC of INDAER concluded that had he been aware of the Natural Hazards paper he would have rejected the submission, and did not accept the explanations of the authors regarding the reasons for overlap. I have informed Springer that we are recommending retracting the article. I have not received a response from the authors to the letter informing them of the decision to retract. INDAER_174C_141–151, https://www.sciencedirect.com/science/article/pii/S0167610517309030?via%3Dihub .